2006
DOI: 10.1103/physrevb.74.235437
|View full text |Cite
|
Sign up to set email alerts
|

Chemical ordering and composition fluctuations at the (001) surface of theFe64Ni36Invar alloy

Abstract: We report on a study of (001) oriented fcc Fe-Ni alloy surfaces which combines first-principles calculations and low-temperature STM experiments. Density functional theory calculations show that Fe-Ni alloy surfaces are buckled with the Fe atoms slightly shifted outwards and the Ni atoms inwards. This is consistent with the observation that the atoms in the surface layer can be chemically distinguished in the STM image: brighter spots (corrugation maxima with increased apparent height) indicate iron atoms, dar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
3
4
0
Order By: Relevance
“…2). The dark spots are similar to the Ni atoms on the Fe-Ni alloy observed by Ondráček et al 12) and are distributed randomly on the surface with about 41% coverage. The AES spectra shows the marked decrease of Fe from the surface (Fig.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…2). The dark spots are similar to the Ni atoms on the Fe-Ni alloy observed by Ondráček et al 12) and are distributed randomly on the surface with about 41% coverage. The AES spectra shows the marked decrease of Fe from the surface (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…They found that the Fe atoms appear as bright spots while the Ni atoms appear as dark spots on the Fe-Ni alloy surface. 12) In the present study, we observed that the elongated bcc-Fe domains disappear and a triangular network structure and large accumulated bcc-Fe islands are formed on the surface after heating at 550 K [ Fig. 2(a)].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…25 Fe atoms is clearly visible (see Section 4.1), suggesting that the surface layer can be regarded as a Ni x Fe y O single layer. This interpretation is also supported by the presence of a strong peak in STS spectra detected at about 0.25 eV below E F , very similar to the resonance observed in spectra acquired on invar alloys [259]. 1 4.3.…”
Section: Wetting Layer Oxides On Fe(001)supporting
confidence: 78%
“…At the center of the Brillouin zone, the local density of states decays slowest towards the vacuum and contributes presumably largest to the tunnel current [20]. By assuming the magnetization perpendicular to the surface, it is found that, without relaxation or without spin-orbit interaction, the spin polarizationP of the surface atoms is fully aligned with the magnetization direction, thus forming a collinear spin structure.…”
mentioning
confidence: 98%